DESIGNING ENGLISH READING TEXTS BASED ON "MBABA BELO SELAMBAR" FROM KARO LAND - Yeni Verawati Meha; Evi Novalin Bako; Novina Estetica Br Gurusinga (ELT (English Language Teaching Prima Journal), 2023)
This research is useful for increasing students' interest in reading through the local cultural reading text "Mbaba Belo Selambar". This research focuses on the meaning of mbaba belo selambar from Tanah Karo to make a reading text for students so they can be more interested in reading. This research method uses qualitative methods and there are 4 (four) informant subjects in it, consisting of tribal chiefs in Tanah Karo, the bride, the bride's family and the community. Data collection techniques through observation, interviews and documentation. The results of this study show what is the meaning of mbaba belo Selambar in Kutambelin Village, Tiga Panah District, Tanah Karo Regency, designing reading texts through Mbaba Belo Selambar for students in Kutambelin Village, Tiga Panah District, Tanah Karo Regency. The results of this study also lead to students' interest in reading, the influence of local culture on students and researchers will design reading texts in English based on "Mbaba Belo Selambar" in Kutambelin Village, Tiga Panah District, Tanah Karo Regency. Keywords: Reading Text, Mbaba Belo Selambar, Karo Customs, Interest in Reading